Improving Students’ Writing Ability by Using the Inside-Outside Circle Type: The Case of One Senior High School - Ningsih, Retno Wahyu; Elmaida, Elmaida; Adriani, Diyan; Miharti, Isra (Edukasi, 2023)
The student’s writing ability is paramount in every subject, especially English, such as narrative text. At SMK Negeri 10 Merangin in class X Tata Busana, a student’s writing ability is one of the assessment points in the syllabus that has been designed. This research aims to improve students’ writing ability with the Inside-Outside-Circle (IOC) cooperative learning model. The design of this research is Classroom Action Research (CAR). This research was carried out in class X SMK Negeri 10 Merangin for the academic year 2021/2022. In this research, the researcher conducts Learning English writing, which one of the subjects is narrative text. To collect data, the researchers used a written test. The researcher gave a written test to the students, namely the pre-test, using analytical scores in analyzing the written test. Based on the research results, none of the students achieved the KKM score. In the first cycle, 44% or six students scored >75, and 56% or 13 students scored <75. Furthermore, in the second cycle, 89%, or 13 students achieved the KKM, and 11% or six students did not reach the KKM. Furthermore, the student’s average score in the pre-test was 33.78%, in the first cycle 50.52%, and in the second cycle 64.57%. Based on these findings, the researcher concludes that this research can improve students' writing ability by using the inside-outside-circle (IOC) type in class X students at SMK Negeri 10 Merangin. Based on these data, the researcher would like to conclude that students' writing ability has improved from the tests that have been given, but students to be more active in learning to write about vocabulary and mechanics and grammar.